2021
DOI: 10.1111/jan.14800
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality for limb motor function, balance, gait, cognition and daily function of stroke patients: A systematic review and meta‐analysis

Abstract: Aims To explore the beneficial effects of virtual reality (VR) interventions on upper‐ and lower‐limb motor function, balance, gait, cognition and daily function outcomes in stroke patients. Design A systematic review and meta‐analysis of randomized controlled trials. Data Sources English databases (PubMed, EMBASE, the Cochrane Library, CINAHL, Web of Science, Physiotherapy Evidence Database, ProQuest Dissertations and Theses) and Chinese databases (Chinese BioMedical Literature Service System, WANFANG, CNKI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 89 publications
9
71
2
7
Order By: Relevance
“…However, our pooled results showed no significant benefits of VR in improving global cognitive function for patients with stroke. Our result was comparable to recently published meta-analysis reviews by Wiley et al [ 39 ] and Zhang et al [ 40 ], who reported that VR therapy is not superior to control interventions in improving global cognition in individuals with stroke. This result differs from another systematic review [ 25 ], which only included 4 studies published in 2018.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, our pooled results showed no significant benefits of VR in improving global cognitive function for patients with stroke. Our result was comparable to recently published meta-analysis reviews by Wiley et al [ 39 ] and Zhang et al [ 40 ], who reported that VR therapy is not superior to control interventions in improving global cognition in individuals with stroke. This result differs from another systematic review [ 25 ], which only included 4 studies published in 2018.…”
Section: Discussionsupporting
confidence: 90%
“…However, current evidence fails to support the effects of VR-based therapies in improving global cognitive function, attention, verbal fluency, depression, and the QoL. Unlike prior systematic reviews [ 8 , 25 ] primarily focused more on either one type of VR, such as exercise-based VR, or one aspect of cognition indicators, such as only global cognitive function, our review [ 40 ] comprehensively evaluated the effect of VR-based therapies on global and domain-specific cognition and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many clinical studies favored VR-based intervention for motor function, balance, gait, and activities of daily living (ADL) in patients with stroke. Although multiple systematic reviews and meta-analyses have indicated that VR-based training was useful for upper limb motor function, lower limb motor function, balance, gait, and activities of daily living (ADL) in stroke ( Henderson et al, 2007 ; Laver et al, 2011 ; Saposnik et al, 2011 ; Lohse et al, 2014 ; Laver et al, 2015 ; de Rooij et al, 2016 ; Li et al, 2016 ; Silver, 2016 ; Yates et al, 2016 ; Laver et al, 2017 ; Aminov et al, 2018 ; Al-Whaibi et al, 2021 ; Fang et al, 2021 ; Peng et al, 2021 ; Zhang et al, 2021 ), two recent articles published in The Lancet Neurology by Saposnik et al (2016) and Silver (2016) argued that the methodological issues that existed in some of the studies ( Broeren et al, 2008 ; Kwon et al, 2012 ) were the comparison of VR combined with conventional rehabilitation vs. conventional rehabilitation alone without active control. Such study design ( Saposnik et al, 2011 ; Lohse et al, 2014 ; Laver et al, 2015 ) might create an imbalance in the total rehabilitation time, and the effect might be induced by any active intervention and might not be explained by VR ( Saposnik et al, 2016 ; Silver, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-immersive VR (niVR) is considered more accessible and inexpensive than iVR and enables patients to visualize virtual environments in 2D projected onto a screen and interact with them through the use of a mouse, keyboard or joysticks [33,34]. VRBT is considered a useful intervention along with CT for neurological [35] or musculoskeletal disorders [36] that can be used at home, thereby favoring patient accessibility to physiotherapy protocols (telephysiotherapy), which has been especially important during the COVID-19 pandemic [37].…”
Section: Introductionmentioning
confidence: 99%